PENGARUH KOMPETENSI, BEBAN KERJA, SERTA MOTIVASI TERHADAP KINERJA PERAWAT HOMECARE (Survei pada perawat homecare di Kota Bandung) - Ahmad Jaelani, AJ (2020)
Ahmad Jaelani (1706770) "The Effect of Competence, Workload, and Motivation on the Performance of Homecare Nurses in the City of Bandung". Under the guidance of Prof. Dr. H. Eeng Ahman, MS, and Dr. Hady Siti Hadijah, S.Pd., M.Sc. This study aims to find a picture of competence, workload, and motivation on performance and how the influence of competence and workload on the performance of homecare nurses in the city of Bandung. The research method used in this research is descriptive and explanatory survey with a total sampling technique. Respondents in this study were homecare nurses in the city of Bandung with a sample of 99 people. The data analysis technique used is path analysis with SPSS 25.0 computer software tools. Hypothesis testing uses t-statistic test. Whereas R² is used to find out how the influence of the independent variables together on the dependent variable. The results of this study indicate that competency, workload and motivation are in the high category, while the performance is in the very high category. Statistical test results show that together competency, workload and motivation have a positive and significant effect on the performance of homecare nurses. Partially, competence has a positive effect on motivation, while workload negatively affects motivation. Partially, competence has a positive effect on performance, while workload has a negative effect on performance. And partially, motivation has a positive and significant effect on the performance of homecare nurses in Bandung Keywords: Competence, Workload, Motivation, Performance, Homecare